Contemporary Islamic Moderation: Insights from al-Qaradawi, Nurcholis Madjid, and Abdurrahman Wahid - Rafida, Alifa Ihfazna; Sahri, Sahri; Amin, Faizal (ISTIFHAM, 2025)
The concept of Islamic moderation has gained increasing relevance in response to the global rise of religious extremism and socio-political intolerance. This article explores the moderate Islamic thought of three influential contemporary scholars: Yusuf al-Qaradawi, Nurcholish Madjid, and Abdurrahman Wahid. Each offers distinct yet complementary interpretations of moderation, bridging normative Islamic teachings with contemporary societal contexts. Their approaches emphasize tolerance, pluralism, and constructive engagement with modernity. Using a comparative and qualitative methodology grounded in primary sources and interpretive traditions, this study uncovers the epistemological foundations of their views. Despite differing cultural and political backgrounds, all three thinkers consistently advocate for the principle of wasatiyyah (the middle path) as both a theological and sociological framework. Their contributions provide a normative basis for educational reform, interfaith dialogue, and the cultivation of civic ethics in pluralistic societies.